Green Banking Trends in Islamic Bank: Gen Z’s Awareness and Knowledge - Adha Herfian Prayogi; Nihayatu Aslamatis Solekah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The concept of green banking is a concern of financial institutions today, including Islamic financial institutions. Because with this concept, banks are expected to be able to have a positive impact on the environment, both in bank operational activities as well as credit and loans provided to customers. The background of this research is to find out how much awareness generation z has to use Islamic bank services based on their attention to the environment. As well as knowing the extent of the influence of their knowledge about green banking in the interest in using Islamic bank services. In this study, a quantitative method was used using the hair formula to determine the number of samples to be used. This hair formula is to determine the number of samples that are not known with certainty, so that 135 samples of generation z of Malang city are obtained randomly with this research method using nonprobability nonprobability sampling. The data was processed using SPSS. The results showed that interest in using Islamic bank services was positively and significantly affected by the green banking knowledge variable, while awareness had no effect on interest in using Islamic banking services.